PENGARUH INQUIRY TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN ILMU PENGETAHUAN ALAM DI SEKOLAH DASAR - Nazariah, Mustri; Kartono, Kartono; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this study was to determine the effect of inquiry method on student learning outcomes in science lessons in class V SDN 16 Pontianak Kota. The experimental research used quasi experimental design type Nonequivalent Control Group Design. The sample in this research is class V A totaling 27 students. The technique used in data collection is measurement. Data collection tool used is a test with the type of written test in the form of objective amounted to 40 questions. Based on calculation of mean statistic of control class learning result 60,76 and average result of experiment class study 75,85, result of hypothesis test of data (t-test) obtained t_hitung (5,959)> t_tabel (2,054), significant level (α = 5%) of 2.054, then Ha is accepted which means there is influence of inquiry method toward student learning outcomes in science learning in class V SDN 16 Pontianak Kota. From the calculation of effect size (ES) obtained by 1.41, it means that the learning with the inquiry method gives a high influence on the students' learning outcomes in science lesson in class V SDN 16 Pontianak Kota. Keyword : Inquiri Method, Study Result, Natural Science